Clinical Characteristics and One-Year Survival of Cancer Patients Presenting to Emergency Department - (:unkn) unknown (AKAD DOKTORLAR YAYINEVI, 2009)
The objective is to define the characteristics of cancer patients in the Emergency Departments (ED), and determination of one-year survival. A retrospective survey of the patients referred to our University-based ED in one year diagnosed with neoplasm was conducted. Patient information regarding demographics, chief complaints, findings and survival were gathered from hospital registry, health administration and by telephone survey. The sample comprised 174 patients of whom, 29 had received the diagnosis in the ED. 83.4% of these visits were oncology-related. The most common complaint of 29 newly diagnosed patients in the ED were pain (48%), dyspnoea (13%). Lungs were the most commonly involved organ. The majority of the patients harbored advanced disease. Cases in the distant stage were 12.69 times more likely to report oncology-related symptoms (ORS) than cases with localized cancer and cases with regional cancer were 7.12 times more likely than localized cases. 83% of patients with ORS died within one year. Male patients, those with ORS, and distant stage had significantly shorter survival. Cancer patients are referred to ED due to pain and dyspnoea resulting from advanced disease. Emergency physicians should have protocols shared with the relevant disciplines as to the management of commonly encountered problems of cancer patients.
Keywords: Oncology; Cancer; Survival; Emergency; ONCOLOGIC EMERGENCIES; SYMPTOMS; DISEASE